COVID‐19, chronicle of an expected pandemic - Philippe J Sansonetti (EMBO Molecular Medicine)
Graphical Abstract What is COVID‐19? What are the causes, parameters, and effects of this disease? What are the short‐ and long‐term prospects? Philippe Sansonetti, Infectious disease specialist and Chief Editor of EMBO Molecular Medicine, explains why the fate of the epidemic is in our hands.